PERFORMANCE OF IMPACT OF MAHATMA GANDHI NATIONAL RURAL - SHRAWANI SHYAMAL (International Journal of Multidisciplinary Research and Studies, 2020)
A Plan of this Kind has Very Few Analogs Anywhere Else in the World. Plan Jefes y de Hogar was Argentina's first national job-creation programme, and it was launched in the year 2002. It was a start towards reviving the economy with a concentration on municipal regions as the primary target. It included things like volunteering in the community, taking care of children, improving one's health, getting an education, and starting one's own business. However, by the year 2006, the Scheme had essentially become a poverty and employment insurance scheme. In contrast, the MGNREGA was designed to be more complicated from the beginning, with the overarching goals of increasing wage employment and strengthening natural resource management through works that addressed causes of chronic poverty such as drought, deforestation, and soil erosion.